A Bibliometric Review of Customer Experience-Based Financial Strategies (West Science Interdisciplinary Studies, 2025)
Customer experience (CX) has emerged as a critical component of strategic planning within the financial services industry, driving value creation through personalization, loyalty, and operational efficiency. This study conducts a bibliometric review to map the intellectual landscape of customer experience-based financial strategies using data extracted from the Scopus database and analyzed through VOSviewer. A total of 502 articles were evaluated using co-authorship, citation, keyword co-occurrence, and country collaboration analyses. The results reveal that central themes such as customer satisfaction, finance, and financial services form the conceptual core of the field, while recent trends emphasize digital transformation, fintech, and artificial intelligence. Prominent scholars and methodological influences shape the field’s theoretical base, with the United States and India identified as key contributors to global research collaboration. The study highlights the evolution of the domain from service quality models to AI-enabled customer engagement, and identifies opportunities for future research in cross-cultural contexts, empirical validation, and ethical dimensions of digital CX strategies.